2021
DOI: 10.1001/jamaoncol.2021.4761
|View full text |Cite|
|
Sign up to set email alerts
|

Treatment Outcomes and Safety of Mobocertinib in Platinum-Pretreated Patients With EGFR Exon 20 Insertion–Positive Metastatic Non–Small Cell Lung Cancer

Abstract: IMPORTANCEMetastatic non-small cell lung cancer (mNSCLC) with EGFR exon 20 insertion (EGFRex20ins) mutations is associated with a poor prognosis. Mobocertinib is an oral tyrosine kinase inhibitor designed to selectively target EGFRex20ins mutations.OBJECTIVE To evaluate treatment outcomes and safety of mobocertinib in patients with previously treated EGFRex20ins-positive mNSCLC.DESIGN, SETTING, AND PARTICIPANTS This 3-part, open-label, phase 1/2 nonrandomized clinical trial with dose-escalation/dose-expansion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
203
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 208 publications
(253 citation statements)
references
References 29 publications
7
203
0
Order By: Relevance
“…Unlike previously approved reversible and irreversible inhibitors, mobocertinib has shown the ability to bind and inactivate the compact ATP-binding site of EGFR Ex20ins mutants that was shown to be inaccessible to most compounds [ 75 ]. Approval was based on results from an international, non-randomized, open-label, multicohort EXCLAIM clinical trial (NCT02716116), which evaluated mobocertinib efficacy in a cohort of 114 NSCLC patients carrying EGFR Ex20ins mutations that have progressed on or after platinum-based chemotherapy [ 76 , 77 , 78 ]. Patients were administered with mobocertinib 160 mg orally daily until disease progression or intolerable toxicity.…”
Section: Egfr Ex20ins Targeted Therapiesmentioning
confidence: 99%
“…Unlike previously approved reversible and irreversible inhibitors, mobocertinib has shown the ability to bind and inactivate the compact ATP-binding site of EGFR Ex20ins mutants that was shown to be inaccessible to most compounds [ 75 ]. Approval was based on results from an international, non-randomized, open-label, multicohort EXCLAIM clinical trial (NCT02716116), which evaluated mobocertinib efficacy in a cohort of 114 NSCLC patients carrying EGFR Ex20ins mutations that have progressed on or after platinum-based chemotherapy [ 76 , 77 , 78 ]. Patients were administered with mobocertinib 160 mg orally daily until disease progression or intolerable toxicity.…”
Section: Egfr Ex20ins Targeted Therapiesmentioning
confidence: 99%
“… 140 Later, in September, the approval of mobocertinib (TAK‐788) was based on Study 101, in which mobocertinib showed an ORR of 28% with a median response duration of 17.5 months. 68 …”
Section: Targeted Therapy For Nsclcmentioning
confidence: 99%
“…Mobocertinib is granted a BTD from the U.S. FDA for NSCLC with EGFR or HER2 exon 20 insertion mutations, based on the data from a phase II trial. 68 Despite the approval of fam‐trastuzumab deruxtecan‐nxki (Enhertu), other inhibitor targeting HER2 showed promising effects on NSCLC. Poziotinib, an oral irreversible pan‐HER TKI, demonstrated a promising ORR of 35.1% in HER2‐ mutated NSCLC in a phase II trial, ZENTITH20‐2.…”
Section: Other Promising Therapies For Nsclcmentioning
confidence: 99%
“…The most common treatment-related AEs were QTc prolongation, rash, and diarrhea occurring in 60.9%, 43.5%, and 21.7%, respectively. Mobocertinib is a novel small-molecule TKI designed against exon 20 insertions; in a phase I/II clinical trial, mobocertinib showed promising antitumor activity in previously treated NSCLC patients with EGFR exon 20 insertions, resulting in "breakthrough therapy designation" by the U.S. Food and Drug Administration (FDA) [76,77]. Preclinical data indicate that mobocertinib is highly selective, as it possesses the lowest HER2 exon 20 insertion/wild-type EGFR IC50 ratio.…”
Section: Targeting Her2 In Nsclcmentioning
confidence: 99%